O-041 Data from the ESHRE PGT consortium – year 2020. (30th June 2022) - Van Montfoort, A; De Rycke, M; Carvalho, F; Rubio, C; Bronet, F; Spinella, F; Goossens, V
Abstract: Study question: Which are the trends shown in data collection XXII of the European Society of Human Reproduction and Embryology (ESHRE) PGT Consortium compared with previous years? Summary answer: Data collection XXII, year 2020, represents valuable data on PGT activity in (mainly) Europe and reports on the main trends observed, being the further expansion of comprehensive testing technology in PGT-SR and PGT-A. What is known already: The ESHRE PGT Consortium was set up in 1997 and from that time has been collecting data on PGT and PGT-A. The PGT database comprises the world's largest collection of PGT / PGT-A data providing a valuable resource for data mining and for following trends in PGT practice. So far, up to the year 2015, data collections were carried out in a retrospective data way, from 2016 onwards a prospective cycle-by-cycle data collection was in place. Study design, size, duration: As the nature of PGT/ PGT-A treatments has changed significantly over the last years and IVF cycle management and genetic analysis techniques are getting more complex, ESHRE uses an online data collection system in which data are collected prospectively from oocyte retrieval to analysis, embryo transfer and pregnancy / live birth. Data are collected cycle by cycle on a voluntary basis. Participants/materials, settings, method: For the 2020 data, individual centres (37) from 20 countries directly entered the data into the PGT database through software developed by ESHRE. Data were analysed at ESHRE headquarters and include all aspects of PGT/PGT-A cycles. Main results and the role of chance: The Consortium has analysed the PGT analyses (n = 2809) performed in 2020. The indications for PGT included inherited chromosomal abnormalities (n = 331 analyses), monogenic disorders (n = 987 analyses), aneuploidy testing for infertility (n = 1417 analyses) or combinations of the above (n = 74 analyses). In addition, 704 clinical pregnancies and 335 deliveries have been analysed in detail. The methods used for biopsy were polar body (2%), cleavage stage biopsy (20%) and blastocyst biopsy (78%), showing a further increase of blastocyst biopsy compared to 2019. The methodology used for diagnosis is what is evolving most over the last years, with data set XXII (2020) showing around 4% of FISH, 28% of PCR and 68% of WGA. Within WGA 95% of the analysis were done using NGS, in 4% of the cases SNP arrays were used and in 1% array-CGH was used. The overall clinical pregnancy rate is about 25% per analysis. The baby data show that it is difficult for most centres to have a detailed follow-up. Limitations, reasons for caution: The findings apply to the 37 participating centres and may not represent worldwide trends in PGT. Data were collected prospectively, but details of the follow-up on PGT pregnancies and babies born were limited. Wider implications of the findings: The ESHRE PGD Consortium continues its activities as an important forum for PGT practitioners to share data and exchange experiences. The information extracted from the data collections helps to monitor quality issues in PGT and survey the introduction and effectiveness of new PGT technologies and methods. Trial registration number: